Exploring Caregiver Burden of Thalassemia Major Patients - Yasmeen, Humaira; Khan, Hubza Ruatt; Hasnain, Shahida (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Thalassemia requires lifelong therapy that continuously strains patients, their families, and the local health system. This study was designed to analyse the challenges faced by carers and the effect they have on their social, psychological, and personal lives. Two hundred parents (100 cases and 100 controls) were recruited. In addition to socioeconomic status and concerns, feelings about children and their state of depression were also recorded by the PHQ-9 instrument. Statistically significant correlations were found which showed that parents are exposed to trauma at a very early age which limits their ability to become effectual individuals. Therefore, training and counselling must be worked out with extended family members for whom the health care body should also play its part in alleviating their sufferings. Overall, this study emphasized the significance of considering caregiver worries regarding improving the well-being of children.